Identification and comparison of protein composition of biofilms in response to EGCG from Enterococcus faecalis and Staphylococcus lugdunensis, which showed opposite patterns in biofilm-forming abilities - Jung-Ah Cho; Sangsoo Jeon; Youngmin Kwon; Yoo Jin Roh; Sukjin Shin; Chang-Hun Lee; Sung Jae Kim (Biofilm)
Bacterial biofilm is resistant to conventional antibiotic treatments, leading to complications associated with many infection-related human diseases. Epigallocatechin Gallate (EGCG), a phenolic catechin enriched in green tea, is recognized for its anti-bacterial and anti-biofilm activities. In this study, we examined the protein components of the biofilms formed in the absence or presence of EGCG using Enterococcus faecalis and Staphylococcus lugdunensis, which had shown opposing patterns in biofilm formation. A clustering heatmap revealed that the two microorganisms expressed the different protein sets in response to EGCG. Proteins that were noticeably upregulated included those associated with stress responsiveness and gluconeogenesis in E. faecalis, and gene modification in S. lugdunensis. Conversely, downregulated proteins were related to tRNA-modifying enzyme activity in E. faecalis, and anabolic metabolism in S. lugdunensis. Among the proteins identified only in EGCG-responsive biofilms, enzymes involved in de novo purine biosynthesis were enriched in E. faecalis, while proteins likely to cause DNA instability and pathogenicity changes were abundantly present in S. lugdunensis. The classification based on gene ontology (GO) terms by microorganism exhibited that metabolic process or catabolic activity was at the top rank in E. faecalis with more than 33 proteins, and in S. lugdunensis, localization or transport was highly ranked with 4 proteins. These results support the hypothesis that EGCG might cause different cellular programs in each microorganism. Finally, comparison of the proteomes between two groups that form biofilms to similar extents discovered that 2 proteins were commonly found in the weak biofilm-forming groups (E. faecalis and EGCG-responding S. lugudunensis), whereas 9 proteins were common among the strong biofilm-forming groups (S. lugdunensis and EGCG-responding E. faecalis). It was suggested that these proteins could serve as potential indicators to detect the presence and predict the extent of biofilm formation by multiple microorganisms. Taken all together, proteomics data and analyses performed in this study provided useful and new information on the proteins embedded in the biofilms formed at the specific conditions, which can aid in diagnosis and the development of tailored treatment strategies.